Kinetic energy transfer during the tennis serve - de Subijana, C. L.; Navarro, E. (Biology of Sport, 2010)
Several studies have established the pattern used in the over arm hitting and throwing movements, however to date there has not been one which statistically expresses the Kinetic Link Principle of the tennis serve. The main goals of this study were: first to investigate the kinetic energy transmission pattern using a complete mechanical body model and second, to create a tool which could help evaluating the individual technique of a tennis player. This tool was a statistical procedure which expressed the individual technique of a player as a mathematical function. Fourteen and twelve flat tennis serves of two top tennis players landing in an aiming area were recorded with two synchronized video cameras at 125 Hz. The experimental technique was 3D photogrammetry. A 28 points body model with five solid-rigid (the pelvis, the thorax, the upper arms and the racquet) was built. The kinetic energies from the body segments were considered the biomechanical parameters. The mean speeds of the balls were 41.9 m/s (150.9 km/hr) and 38.1 m/s (137.2 km/hr). A Kinetic Sequential Action Muscle principle based on the kinetic energy transfer was probed statistically by mean a correlation analysis. This pattern showed the existence of a proximal to distal sequence of kinetic energy maximums. A significant (p<0.05) discriminant function for each player could predict the category of the serve ("good" or "bad") in the 78.6% and 100% of the cases. This function facilitated the understanding of the individual technique of a tennis player showing that this could be a tool for the tennis training complementary to the qualitative (observational) analysis.